2004
DOI: 10.1111/j.1460-2695.2004.00784.x
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring fatigue degradation in austenitic stainless steels

Abstract: A B S T R A C T During cyclic loading of austenitic stainless steel, microstructural changes occurred, which affected both mechanical and physical properties. For certain steels, a strain-induced martensitic phase transformation was observed. The investigations showed that for the given material and loading conditions the volume fraction of martensite depended on the cycle number, temperature and initial material state. It was found that the martensite content continuously increased with the cycle number. Ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 6 publications
1
20
0
1
Order By: Relevance
“…In this sample, almost all transformation is completed gradually by small events. This result is in agreement with previous works [1,11,14]. Kalkhof showed that for the given material and loading conditions the volume fraction of martensite depended on the cycle number.…”
Section: Clustersupporting
confidence: 94%
See 1 more Smart Citation
“…In this sample, almost all transformation is completed gradually by small events. This result is in agreement with previous works [1,11,14]. Kalkhof showed that for the given material and loading conditions the volume fraction of martensite depended on the cycle number.…”
Section: Clustersupporting
confidence: 94%
“…Since the displacive MT modifies the volume (with ␥ → ␣ martensite a volume expansion occurs [2]), internal stresses are generated that can affect the lifetime of components subjected to fatigue. Thus the monitoring of MT is of societal interest and many non-destructive techniques have been applied, among which eddy current testing [13,14] and acoustic emission [15,16]. The aim of this study is to investigate MT by AE and MT in 304L steel during fatigue tests, using two kinds of analysis: pattern recognition and power-laws statistics, which we shortly describe hereunder.…”
Section: Introductionmentioning
confidence: 99%
“…From the comparative studies in this paper, it is shown that the AISI 303 stainless steel undergoes a significant additional hardening under non‐proportional loading. Through a close comparison with the cyclic behaviour of AISI 304 stainless steel, 4–6,19,20 which has a similar increase in hardening, it is suggested that this occurs because of the gamma to alpha prime phase transformation. AISI 303 stainless steel is likely to be unstable under low‐cycle fatigue and some gamma to alpha prime phase transformation may take place under cyclic loading.…”
Section: Resultsmentioning
confidence: 96%
“…Among the structural steels, stainless steels have very special cyclic behaviour and microstructural changes under cyclic loading, which affect both mechanical and physical properties. In the literature, several researchers (for example, McDowell et al , 4 Kalkhof et al , 5 Chen et al 6 ) published research data about the transformation of gamma to alpha prime phase and additional hardening of AISI 304 stainless steel. But no research paper was found for AISI 303 stainless steel with a higher carbon content, to the knowledge of the authors.…”
Section: Introductionmentioning
confidence: 99%
“…The corresponding changes of magnetic properties can be detected by measuring the eddy current impedance, the magnetic permeability and the remanence field. These methods have been extensively investigated by several research groups in the last decade [5][6][7][8][9][10][11][12][13]. It was shown that in meta-stable ASS a 0 -formation can be used as an indication of the fatigue state, if the conditions listed below are fulfilled [4]:…”
Section: Introductionmentioning
confidence: 99%